In situ characterization of phase transformations in petroleum pitch by high temperature X-ray diffraction. (1st January 2023) - Vautard, F.; Cakmak, E.; Arnould, M.; Watkins, T.R.; Paul, R.; Meyer, H.; Damron, J.; Gallego, N.; Lara-Curzio, E.
Graphical abstract: Highlights: Isotropic to mesophase pitch transition monitored by in situ X-ray diffraction. Kinetics of the transformation described by Avrami's equation. Characterization of molecular weight distribution before and after mesophase generation. Abstract: The phase transformation from isotropic to mesophase of a petroleum-derived pitch was monitored by in situ X-ray diffraction at 410 °C. The kinetics of the transformation were characterized by monitoring the growth of a broad peak at 2θ∼24° and could be described by Avrami's equation. The volatilization of low molecular weight components originally present in the pitch, or produced during the condensation reaction, was assessed by thermal gravimetry analysis, following the same thermal history. Ex situ characterizations of the pitch precursor before and after thermal treatment provided insight into the evolution of the molecular structure associated with mesophase generation (optical polarized microscopy, molecular weight distribution by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry, X-ray photoelectron spectroscopy, Auger spectroscopy, and thermal stability). This investigation demonstrates the value of using complementary in situ and ex situ experimental techniques to characterize complex mechanisms during the processing of organic materials.